Aktualisasi Ajaran Islam Dalam Kehidupan Modern: Perspektif Muhammadiyah Terhadap Agama dan Budaya - Anjas Ardana; Hazizah Isnaini; Kharisma Azam Rangkuti; Rizky Aditya; Yuspan Zaelani; Selamat Pohan (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study examines Muhammadiyah's perspective on the relationship between religion and local culture in Indonesia, as well as how the organization actualizes Islamic teachings in community life. The introduction highlights Indonesia's position as the world's largest Muslim-majority country, with a history of Islamic organizations such as Muhammadiyah, founded to purify Islamic teachings based on the Al-Qur'an and Hadith, while facing challenges from the interaction between religion and local culture, often regarded as bid'ah (innovation in religion) or takhayul (superstition). The main challenge is how Muhammadiyah selects, assimilates, and integrates local culture so that Islamic teachings are not merely theoretical but relevant to the socio-cultural context. This study employs a library research approach, analyzing reliable sources to provide a comprehensive understanding. The research results define culture as a complex construct involving human thoughts, customs, and habits, while Islam is viewed as a universal teaching that regulates relationships between humans, God, fellow beings, and nature. Muhammadiyah's perspective sees religion as complete and perfect, which must be contextualized with contemporary developments, while culture is recognized as part of human nature that needs to be selected to align with Islamic law (syariat). Integration is carried out through principles of selecting positive cultural elements, adaptation, and using arts and culture as a medium for da'wah (Islamic propagation), grounded in the principle of